Examining the impact of Industry 5.0 on economic sustainability: A hybrid SEM-ANN approach - ALSHAMSI, SAIF RASHED (2023)
While there is an existence of a significant amount of literature studies on industrial revolution there exist a scarce knowledge about examining the impact of Industry 5.0 on economic sustainability using a hybrid SEM-ANN approach. The study aims at understanding the impact of industrial 5.0 on economic sustainability. A Quantitative analysis was done with data collected from over 363 participants. Two stage analytical techniques were applied in this work which involves the combination of ANN and with the PLS-SEM. First, PLS-SEM is used to enable understand the predictors and their significant influence on the sustained use of industrial 5.0 revolution. The results show that there is a positive and non-significant relationship between predictors and industrial 5.0 revolution on sustainability. The outcome of this study as provided valuable insight for those countries willing to adopt industrial 5.0 revolution to understand its impact on economic sustainability.